Stingless bee honey harvesting system via bluetooth application - Nur Farah Syahira, Ahmad Kamal (2019)
Stingless bees are by far the largest group of eusocial bees on Earth. They are small insects of dark bee and usually do not sting. Despite that, this type of bees also collecting nectar from flowers produce and convert it into honey. Honey is produced by a process of regurgitation by honey bees which is stored in the beehive. A beekeeper use a honey harvesting system that use a vacuum pump to extract honey from the beehive. The harvesting system in the market has its own weaknesses. For instance, beekeeper must watch the system do the extraction process in order to not get honey spilled from the bottle as it is a manual systems. Also, a dust particle might be mixing with honey during the extraction process. Honey is very beneficial for our body and regular honey is available to get rid of many diseases. Extracting honey is easier to do when honey is still warm from the beehive as it flows much more freely. New design for the stingless bee honey harvesting system has been made with the availability of Bluetooth technology. The aims of this study were to program a control system to adjust motor speed and stop the system automatically. Subsequent to this, peristaltic pump linkage with oscilloscope to evaluate, compare and validate the motor speed. In this study, the application were found connected with the honey harvesting system. This application can be used to harvest honey, the sensor can detect the presence of honey in the bottle and motor works well when changing the speed motor. This honey harvesting system has a good response.